Cameral deposits in a sublethally damaged Pennsylvanian Pseudorthoceras sp. from the Buckhorn Asphalt Lagerstätte in Oklahoma, USA - Seuß, Barbara; Mapes, Royal H.; Klug, Christian; et al. (Annual Meeting of the Paläontologische Gesellschaft, 2010)
The recovery of two well-preserved chambers of the phragmocone of Pseudorthoceras sp. from the Buckhorn Asphalt Lagerstätte provides nw insight into the controversy over how cameral deposits are developed in orthoconic nautiloids. The specimen has two oval openings in the conch, a result of penetrating the outer test and present cameral deposits. The animan survived the attack and was able to still precipitate cameral deposits, astonishing because in the orad chamber the bite-marks opened the chamber to the seawater. Three hypotheses of cameral deposit precipitation can be tested: (1) direct precipitation from the cameral fluid; (2) precipitation from the cameral fluid with a reoccurring organic template/membrane; (3) secretion by a cameral tissue. (1) and (2) cannot be supported because the precipitation chemistry of the cameral fluid is altered and cannot be controlled by the animal. (3) remains possible: the penetration marks would be sealed by cameral tissue regeneration and cameral deposits would be precipitated directly by such tissue. Thus, the cameral fluid chemistry would appear not to be important for cameral deposit precipitation. Anyhow, this hypothesis remains problematic: there are no known openings that would allow tissure connections from the siphuncle through the connecting ring to the cameral deposit